(untitled) (Quest Journal of Management and Social Sciences, 2026)
Background: Digital wallets are rapidly growing in Nepal, offering convenience and cashless payments. Social media provides brands opportunities to engage consumers, share content, and encourage participation. However, research is limited on how social media interactivity influences engagement, value co-creation, and loyalty in developing markets, highlighting a need to explore these dynamics in Kathmandu Valley. Purpose: This study examines how social media brand interactivity affects consumer brand engagement, value co-creation, and brand loyalty among users of digital wallet services in Kathmandu Valley, Nepal. Design/methodology/approach: An explanatory research design based on Service-Dominant Logic was used. A total of 403 respondents were surveyed through a non-probability sampling technique, and partial least squares structural equation modeling (PLS-SEM) was employed to analyze the data. Findings: Cognitive information transfer, entertainment, interactive ease of use, and up-to-date content significantly enhance consumer brand engagement, while customization is non-significant. The model explains 23.4% engagement, 18% value co-creation, and 17% brand loyalty. Conclusion: Digital wallet service providers should enhance social media interactivity by focusing on cognitive information transfer, up-to-date content, interactive ease of use, and entertainment. Encouraging customer feedback, opinions, and referrals helps co-create value and strengthen brand loyalty. These findings provide practical guidance for improving social media strategies to engage and retain consumers in developing markets such as Nepal. Keywords: Brand interactivity, engagement, Co-creation, social media, digital wallets, Kathmandu Valley Nepal